2011
DOI: 10.1038/srep00081
|View full text |Cite
|
Sign up to set email alerts
|

Location, location, location: Beneficial effects of autologous fat transplantation

Abstract: Visceral adiposity is a risk factor for cardiovascular disorders, type 2 diabetes mellitus (T2D) and associated metabolic diseases. Sub-cutaneous fat is believed to be intrinsically different from visceral fat. To understand molecular mechanisms involved in metabolic advantages of fat transplantation, we studied a rat model of diet-induced adiposity. Adipokine genes (Adiponectin, Leptin, Resistin and Visfatin) were expressed at 10,000 to a million-fold lower in visceral fat depot as compared to peripheral (thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 49 publications
3
32
0
Order By: Relevance
“…This result reflects a sexual dimorphism in body fat distribution [12]. Females deposit relatively more fat in subcutaneous/inguinal depots, which has beneficial effects on the control of body weight and metabolism [13]; on the other hand, males tend to deposit more fat in intra-abdominal/gonadal depots, which has been found to be related to risk for a number of diseases [14]. …”
Section: Resultsmentioning
confidence: 99%
“…This result reflects a sexual dimorphism in body fat distribution [12]. Females deposit relatively more fat in subcutaneous/inguinal depots, which has beneficial effects on the control of body weight and metabolism [13]; on the other hand, males tend to deposit more fat in intra-abdominal/gonadal depots, which has been found to be related to risk for a number of diseases [14]. …”
Section: Resultsmentioning
confidence: 99%
“…The studies indicated that transplantation of subcutaneous depots into visceral locations improved metabolic parameters, whereas transplantation of visceral depots into subcutaneous locations did not . In addition to metabolic and morphological changes, a striking rearrangement in gene expression towards a subcutaneous signature occurred within three weeks of transplantation (Satoor et al, 2011). Thus, there appear to be both intrinsic and extrinsic forces that regulate adipose depot biology.…”
Section: Reviewmentioning
confidence: 99%
“…An issue in surgical applications is that transplants of adipose depots tend to fail and necrose because of the lack of vascular supply. However, transplanted adipose stem cells recruit vessel formation and the formed adipose depots are well vascularized overcoming the cause of traditional transplant failure (Han et al, 2011;Satoor et al, 2011;Tran et al, 2008).…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, studies in mice have shown that transplantation of SAT from lean mice into the visceral cavity has beneficial effects on body weight, glucose metabolism and insulin sensitivity in lean (Tran et al, 2008) and obese (Foster et al, 2013;Hocking et al, 2015) mice. However, the transplantation of pgWAT to subcutaneous sites has resulted in either no (Barrera et al, 2012;Tran et al, 2008) or some metabolic advantages (Satoor et al, 2011;Tran and Kahn, 2010). Thus, the accumulation of VAT is more harmful than peripheral, subcutaneous obesity, increasing the risk of the development of non-alcoholic fatty liver disease and type 2 diabetes (Fox et al, 2007).…”
Section: Metabolic Risk Is Associated With Individual Adipose Tissue mentioning
confidence: 99%